2009
DOI: 10.1089/jir.2009.0072
|View full text |Cite
|
Sign up to set email alerts
|

Rotavirus and Reovirus Modulation of the Interferon Response

Abstract: The mammalian reoviruses and rotaviruses have evolved specific mechanisms to evade the Type I interferon (IFN) antiviral response. Rotavirus likely represses the IFN response by at least 4 mechanisms. First, the rotavirus protein NSP1, most likely functioning as an E3 ligase, can induce proteasome-dependent degradation of the transcription factors IRF3, IRF5, and IRF7 to prevent their induction of IFN. Second, NSP1 can induce proteasome-dependent degradation of the ubiquitin ligase complex protein beta-TrCP, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
65
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(67 citation statements)
references
References 82 publications
1
65
1
Order By: Relevance
“…The efficiency of cell-to-cell spread for a lytic virus depends not only on the ability of the cell to invoke an antiviral response, but also on the capacity of the virus to counteract it (28,29). For cancer treatment, viruses possessing strong evasion strategies would not be ideal as they likely also infect normal healthy cells.…”
Section: Discussionmentioning
confidence: 99%
“…The efficiency of cell-to-cell spread for a lytic virus depends not only on the ability of the cell to invoke an antiviral response, but also on the capacity of the virus to counteract it (28,29). For cancer treatment, viruses possessing strong evasion strategies would not be ideal as they likely also infect normal healthy cells.…”
Section: Discussionmentioning
confidence: 99%
“…SA11-4F, in contrast with SA11-5S, rapidly degrades the transcriptional factor IRF3 in IECs (43). Whereas RRV NSP1 variably modulated IRF3 in fibroblasts and dendritic cells in a cell type-specific manner (44,45), in preliminary studies, we found RRV signaling through IRF3 was largely intact in RRV-infected HT-29 and HCA-7 cells. Virus was grown in MA-104 cells infected at low multiplicity, and incubated for 72 h in presence of trypsin (0.44 mg/ml), after which cells were lysed by freezing and thawing to achieve virus release.…”
Section: Rotavirus Infectionmentioning
confidence: 65%
“…The genomic dsRNA of GCRV is speculated to be recognized by host sensors for induction of IFN in UVinactivated GCRV-infected CABs (42). In mammals, RIG-I and MDA5 recognize reovirus genome-derived dsRNA that trigger the IFN response, although reovirus dsRNA is rarely seen to be exposed during natural infection (29). Given that there is leaked dsRNA during GCRV replication and that the exposed dsRNA is responsible for induction of IFN and activation of fish PKR, it is hard to understand how PKZ is activated in GCRV-infected cells.…”
Section: Discussionmentioning
confidence: 99%